STATUS KEBERLANJUTAN EKOLOGI PADA PENGELOLAAN HUTAN MANGROVE DI PESISIR ACEH BARAT - Edwarsyah Edwarsyah; Mohamad Gazali (Universitas Teuku Umar, 2015)
Almost mangrove forest in West of Aceh have already been destroyed by Tsunami in 2004. Urgently, we strive to recover the mangrove forest gradually. Prevously, we must study about sustainablity of mangrove forest in West of Aceh. This study aims to analyse the sustainability index and status of mangrove forest in multidimensional scaling. This research was conducted in December to February 2013 in West of Aceh of mangrove coastal. Mangrove Forest Sustainability Index Value of ecological dimensionworth 63.50. The results shown that good enough to used as one tool to evaluate policy Mangrove Forest sector in the region or regions rapidly (rapid appraisal). According to analysis of levelage shown that the high sensitivity of attributes is level of concord of RTRW/RZWP3-K.